2004
DOI: 10.1111/j.0013-0427.2004.00392.x
|View full text |Cite
|
Sign up to set email alerts
|

Do Markets Drive Out Lemmings—or Vice Versa?

Abstract: This paper investigates experimentally a market inspired by two strands of literature: on herd behaviour in non-market situations, and on the aggregation of private information in markets. The first strand suggests that socially undesirable herd behaviour may result when information is private; the second suggests that in a market context the price mechanism may cause the private information to be aggregated correctly and efficiently. This latter therefore suggests that socially undesirable behaviour may be el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 8 publications
1
25
0
3
Order By: Relevance
“…Moreover, in a recent work, Hey and Morone (2004) showed that whenever complexity increases, noise increases as well. Indeed, their results suggest that the volatility of prices is lower (with the implication that herding is less likely) when the quality and quantity of information in the market are higher.…”
Section: Informational Efficiency Of Marketsmentioning
confidence: 99%
“…Moreover, in a recent work, Hey and Morone (2004) showed that whenever complexity increases, noise increases as well. Indeed, their results suggest that the volatility of prices is lower (with the implication that herding is less likely) when the quality and quantity of information in the market are higher.…”
Section: Informational Efficiency Of Marketsmentioning
confidence: 99%
“…In an early study of herd behavior in markets, Hey and Morone (2004) examine whether the market may act as a disciplining device, removing socially undesirable herd behavior through market forces that promote the efficient aggregation of private information. They find evidence of herds developing; either due to bad information, a wrong herd developing, or associated with bubbles/crashes.…”
Section: Herding and Financial Contagionmentioning
confidence: 99%
“…Informational cascades can be viewed as a social phenomenon, hence individual behavior may depend on how the rationality of others is viewed. To this end, Alevy et al (2007) examine a standard informational cascade game, similar to Hey and Morone (2004), to see how market professionals and students respond to uncertainty about the quality of information due to deviations from Bayesian rationality of other participants.…”
Section: Herding and Financial Contagionmentioning
confidence: 99%
“…В 2004 году английские ученые [Hey, Morone, 2004] определенным количеством «акций» и «денег», за плату могли купить (а могли и не купить) зашумленную информацию о том, какими же эти дивиденды будут. При этом они понимали, что полученный ими сигнал верен лишь с определенной вероятностью.…”
unclassified